Digital mentoring process in the Basque non-university education system: mentors' perception - Korres Alonso, Oihane; Paños Castro, Jessica; Arruti Gómez, Arantza (Emerging Trends in Education, 2025)
The development of digital competence is key in the context of the fourth industrial revolution. Thanks to the Next Generation fund of the European Union, different actions are being financed such as the accreditation in digital competence for teachers during the academic year 2022-2023. This research aims to analyze the digital mentoring process with non-university teachers in public schools of the Autonomous Community of the Basque Country. For this purpose, an ad hoc questionnaire was used, which was completed by 27 mentors (50% of the total population), and six of them subsequently answered a semi-structured interview. After analyzing the data with Excel and Atlas.ti, the results highlight the self-motivation of the mentors with technology (proof of this is the self-taught training and the level of digital competence they have), commitment, work overload and the self-perceived need for the program. However, they consider that the relationship and communication with the Public Administration has been scarce, vertical, with little support and constant changes. In addition, they emphasize the need to maintain and recognize the figure of the mentor once the program ends.
Keywords: mentorship; certification; school; teacher digital competence; digitalization